α-Tocopherol reduces oxidative stress in perinatal asphyxia - Rashidul Karim and M. A. Mannan (Bangladesh Pharmacological Society, 2006)
Twenty asphyxiated neonates were studied by estimating reduced gluthathione (GSH) level in red blood cell (RBC) to assess the level of oxidative stress. Neonates were randomly divided into two groups. One group received α-tocopherol (10 mg/kg body weight) once orally daily for 5 days and other group received only vehicle. The mean (± SD) value of GSH in RBC within 24 hrs of age of asphyxiated neonates was 12.26 ± 4.29 mg/dl in untreated group and 11.97 ± 2.34 mg/dl in treated group. After 5 days of asphyxiated neonates (in α-tocopherol untreated group) the GSH level increased to 14.45 ± 3.46 mg/dl whereas in asphyxiated neonates treated with α-tocopherol, it increased to 25.65 ± 4.99 mg/dl indicating 5 days treatment with α-tocopherol among asphyxiated neonates caused approximately two fold increase in GSH level which was statistically significant (P<0.001). This study suggests that α-tocopherol may be useful to reduce the oxidative stress in patients of perinatal asphyxia.